2018
DOI: 10.1101/507814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An increase in spontaneous activity mediates visual habituation

Abstract: The cerebral cortex is spontaneously active, but the function of this ongoing activity remains unclear. One possibility is that spontaneous activity provides contextual information in cortical computations, replaying previously learned patterns of activity that conditions the cortex to respond more efficiently, based on past experience. To test this, we measured the response of neuronal populations in mouse primary visual cortex with chronic two-photon calcium imaging during a visual habituation to a specific … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The only difference observed was a slight increase in active neurons during gray screen epochs that followed the presentation of the familiar visual stimulus, using the activity criteria of ≥10 events ( Table 3). This may reflect an increase in spontaneous neural activity following visual habituation, as previously reported (Miller et al, 2018).…”
Section: The Fraction Of Active Neurons During the Presentation Of Thsupporting
confidence: 77%
“…The only difference observed was a slight increase in active neurons during gray screen epochs that followed the presentation of the familiar visual stimulus, using the activity criteria of ≥10 events ( Table 3). This may reflect an increase in spontaneous neural activity following visual habituation, as previously reported (Miller et al, 2018).…”
Section: The Fraction Of Active Neurons During the Presentation Of Thsupporting
confidence: 77%
“…Visualizing the whole brain requires stepping the probe across ll NeuroResource multiple positions, as recently demonstrated for identifying brain regions involved in the optokinetic reflex in awake mice (Mace ét al., 2018). However, this strategy involves long acquisition time and repetitive presentation of the stimulus at each position, which may hinder animal physiology and trigger habituation (Miller et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we proved the high sensitivity of the vfUSI platform and showed that whisker-evoked hemodynamic responses are detectable in the cortex and the thalamic relay after an experimental session of 30 minutes maximum. Reducing the overall duration of an experiment and the number of stimuli is crucial to preserve proper animal physiology, animal comfort, and avoid the effects of habituation (Miller et al, 2018). Even if vfUSI has a voxel size ~2.5 times lower (~250 µm) compared to 2D fUSI (Figure S4), we were able to detect hemodynamic signals resulting from neuronal activation of functional units such as small individual cortical columns (~100 µm) during stimulation of a single whisker, or microcircuits processing orientation and directional selectivity during visual stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Visualizing the whole brain requires stepping the probe across multiple positions, as it was recently shown to identify brain regions involved in the optokinetic reflex in awake mice (Macé et al, 2018). This strategy, however, results in long acquisition time and repetitive presentation of the stimulus at each position, which may hinder animal physiology and trigger habituation (Miller et al, 2018).…”
Section: Introductionmentioning
confidence: 99%